2021
DOI: 10.46411/jpsoaphys.2021.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Caracterisation Physico-Chimique Et Microbiologique Des Boues De Vidange Deshydratees Et Des Dechets Solides Menagers Organiques Pour Une Valorisation en Compost Agricole

Abstract: In the city of Ouagadougou in Burkina Faso, faecal sludge treatment plants suffer from the lack of a process for recovering sludge after drying. Forsolid household waste, the quantities collected are mainly intended fortechnical landfill. Finding a solution for the recovery of Dewatered Faecal Sludge (DFS) and Organic Household Solid Waste (OHSW) is necessary in order to complete the faecal sludge management and solid waste management sectors. Our work aims to make a physico-chemical, microbiological and eco-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The result of the study is similar to Wong et al (2001) who found that a C/N ratio value around or below 20 is satisfactory. Our results also corroborate with those of Soré (2018) who argued moreover that the C/N ratio for Dewatered Faecal Sludge (DFS) is at 18.99 ± 8.12. However, our results differ from those obtained by Haug (1993) whose results from this work showed that a C/N ratio between 25 and 35 allows for optimal composting.…”
Section: C/n Ratiosupporting
confidence: 92%
See 4 more Smart Citations
“…The result of the study is similar to Wong et al (2001) who found that a C/N ratio value around or below 20 is satisfactory. Our results also corroborate with those of Soré (2018) who argued moreover that the C/N ratio for Dewatered Faecal Sludge (DFS) is at 18.99 ± 8.12. However, our results differ from those obtained by Haug (1993) whose results from this work showed that a C/N ratio between 25 and 35 allows for optimal composting.…”
Section: C/n Ratiosupporting
confidence: 92%
“…This result is in accordance with the ADEME (2006) which confirms that the digestate produced is poor in organic matter [18]. The result of the study is very close to that found by Soré (2018) who shows that the Organic Matter content (%OM) is 25.62 ± 2.59 for Dehydrated Faecal Sludge (DFS).…”
Section: Organic Matter Contentsupporting
confidence: 90%
See 3 more Smart Citations